Museum Van Bommel - Van Dam : Een keuze uit de verzameling van. - Voragen, Thei (Venlo : Museum Van Bommel Van Dam, 1985)
Abram, Ronald ; Backes, Pierre ; Campigli, Massimo ; Damsté, Paul ; Eggen, Gène ; Fast, Marijke ; Gaj, Jacek ; Haagmans, Fons ; van Iepersen, Hans ; Jacobs, Wiel ; Kagie, Jan ; Lammers, Dignum ; Maks, Kees ; Nagy, Imre ; Olde, Hans ; Peeters, Jan ; Raveel, Roger ; Scholten, Luuk ; etc.
Nederlands
kunstcatalogus